Molecular characteristics of glutathione transferase gene family in a neglect medical Spirometra tapeworm - Chen, Wen Qing; Liu, Sha Sha; Cheng, Chi; Cui, Jing; Wang, Zhong Quan; Zhang, Xi (Frontiers in Veterinary Science, 2022)
The Spirometra mansoni is a neglect medical tapeworm, its plerocercoid larvae can parasitize in humans and animals, causing sparganosis. In this study, 17 new members of the glutathione transferase (GST) family were sequenced and characterized in S. mansoni. Clustering analysis displayed the categorization of SmGSTs into two main clades. RT-qPCR illustrated that 7 GST genes were highly expressed in the plerocercoid stage while 8 GSTs were highly expressed in the adult. rSmGST has the typical C- and N-terminal double domains of glutathione transferase. Immunolocalization revealed that natural SmGST is mainly located in the epidermis and parenchyma of plerocercoid, and in the epidermis, parenchyma, uterus and egg shell of adult worm. The optimum activity for rSmGST was found to be pH 6.5 and 25 ℃. The evolutionary tree showed a high level of diversity of cestodes GSTs. SmGSTs contained both conserved family members and members in the process of further diversification. The findings in this study will lay a foundation to better explore the underlying mechanisms of GSTs involved in Spirometra tapeworms.